Editorial: Pathogenic mechanisms, injury biomarkers, prophylaxis and treatment strategy of drug-induced nephrotoxicity - Jiao, Guozheng; Niu, Yimin; Wang, Bin (Frontiers in Medicine, 2024)
Graphical Abstract